2010
DOI: 10.1021/ic101437h
|View full text |Cite
|
Sign up to set email alerts
|

Stable and Tunable Phosphorescent Neutral Cyclometalated Au(III) Diaryl Complexes

Abstract: A series of novel luminescent cyclometalated Au(III) neutral complexes of the type cis-[(N(∧)C)AuL] [N(∧)C = 2-phenylpyridine (ppy), L = 1,1'-biphenyl (1)] and cis-[(N(∧)C)AuL(2)] [N(∧)C = 2-phenylpyridine (ppy), L = C(6)H(5) (2), C(6)F(5) (3), C(6)H(4)-CF(3)-p (4), 2-C(4)H(3)S (5)]; [N(∧)C = 2-(2-thienyl)pyridine (thpy), L = C(6)H(5) (6), C(6)F(5) (7)]; [N(∧)C = 2-(5-methyl-2-thienyl)pyridine (5 m-thpy), L = C(6)F(5) (8)] were successfully synthesized. The X-ray crystal structures of all compounds except 3 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 78 publications
4
74
0
1
Order By: Relevance
“…No oxidation peaks were observed (see Figures S7–S14). The reduction peaks are similar to previously reported mono‐cyclometalated complexes and are ascribed to be a predominately cyclometalating ligand‐centred electrochemical event . Electrochemical data for all final complexes 1 a – 6 b are represented in Table .…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…No oxidation peaks were observed (see Figures S7–S14). The reduction peaks are similar to previously reported mono‐cyclometalated complexes and are ascribed to be a predominately cyclometalating ligand‐centred electrochemical event . Electrochemical data for all final complexes 1 a – 6 b are represented in Table .…”
Section: Resultssupporting
confidence: 84%
“…The onset of degradation ( T d ) for the samples are provided in the Supporting Information (Table S1 and Figures S2–S6) and show similar temperature ranges between 340–365 °C for the complexes bearing 2 ‐ppy as the ligand. Compared with previously investigated mono‐cyclometalated gold(III) complexes bearing two perfluorinated aryls as ancillary ligands, the studied compounds exhibit a thermal stability that was significantly increased by about 70–100 °C.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…We chose to use fluorinated aryl acetylides in most of the complexes, with an anticipation they will improve the stability of the complexes on similar lines of thought as explained for gold(III) biaryl complexes presented in our previous study. 21 All complexes synthesized were found to be stable to air and moisture in the solid state under ambient conditions. Homocoupled products, namely, the butadiynes formed through reductive elimination, were observed as byproduct (confirmed by 1 H NMR and GC-MS studies) in some cases such as for 1a and 3a but were not observed in others, especially for the fluorinated analogues.…”
Section: Methodsmentioning
confidence: 97%
“…The majority of the strategies to obtain emissive Au(III) complexes so far have relied on a tridentate biscyclometalated or a bidentate monocyclometalated ligand scaffold appended to the gold(III) center. 1, 3 Despite the recent progress, very limited success has been achieved on luminescent Au(III) complexes devoid of cyclometalation and the only known ones are cationic in nature. 1a, 4 To the best of our knowledge, there are no luminescent neutral Au(III) complexes that are devoid of cyclometalation.…”
Section: Introductionmentioning
confidence: 99%